PEMBIAYAAN MURABAHAH DI KSPPS BMT NU JAWA TIMUR DALAM PANDANGAN EKONOMI SYARIAH - Syarifuddin, Syarifuddin; Fawaid, Imam; Islam, Faizul (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
Islamic financial institutions in the midst of society have an important role in helping meet community needs, especially murabaha financing products. Where BMT NU already has a plan that has been designed to achieve common goals, before that product is everything that can be offered to customers to get a good response and be able to satisfy customer needs. And the product offered by the Tlogosari Branch of BMT NU is murabahah financing where the BMT NU provides financing to partners who apply for financing to buy goods but lack funds or even have no funds at all by way of installments. This study aims to find out how the murabaha financing contract is implemented at BMT NU Tlogosari Bondowoso branch and to find out the perspective of sharia economic law on murabaha financing contracts at BMT NU Tlogosari Bondowoso branch. This type of research uses qualitative methods to understand the discussion in question. The result of the discussion is that the implementation of the murabaha financing contract at BMT NU Tlogosari is based on the pillars of murabahah and is permissible because it is in accordance with sharia principles.